The Role of Law in Digital Economy Development: Opportunities and Challenges - Junaidi Lubis; Leni Indrayani; Faziatul Amillia Mohamad Basir; Rinaldi, Muammar; Ahmad Braja Wahyu (Outline Publisher, 2024)
This study explores role law in development digital economy with a focus on existing opportunities and challenges. The digital economy, which includes innovation in technology information and communication, has create impact significant in the way business run and service given. However, the development fast technology​ often goes beyond ability regulations to follow, resulting in gap laws that can affect stability and growth this sector. Through studies literature, analysis document law, interviews with experts, and studies case, this study found that framework effective law can facilitate​ growth digital economy by providing clarity law, protect right consumers, and increase investor confidence. However, the challenges main covering need for update more regulation​ frequent and handling difference regulation between countries. Case study from countries like Singapore and Estonia show that approach proactive and adaptive laws can provide​ effective solutions to support​ digital economy. This study recommends the need for further legal reform flexible, improvement collaboration between government, industry, and academia, as well as development policies that can keep up with the pace change technology. This finding is expected to provide outlook valuable for the maker policy, practitioner law, and stakeholders interest other in formulate and implement supporting regulations​ growth digital economy while overcome existing challenges.​